Classical and Keynesian models of inequality and stagnation - Codrina Rada; Daniele Tavani; Rudiger Von Arnim; Luca Zamparelli (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
This paper studies two formal models of long run growth with a medium-run distributive cycle, both of which feature causal links from the rise in inequality to a deterioration of long run macroeconomic performance. Both versions feature an endogenous income-capital ratio: one through the Keynesian notion of effective demand, the other building on induced bias in technical change. A key focus of the analysis is on the assumptions necessary in both frameworks to generate policy implications consistent with the observed decline of the labor share, the income-capital ratio, and labor productivity growth during the neoliberal era. Importantly, both theories: (a) provide space for mutually reinforcing pro-labor and pro-growth policies in the long run, although they differ in the mechanisms at play in these processes; (b) imply a potential tradeoff between pro-labor policies and growth on one hand, and long-run employment on the other; (c) are consistent with the evidence on the distributive cycle at business cycle frequency.
Keywords: E11; E12; E25; E32; O33; O41; 330; Distributive cycle; induced technical change; labor share; stagnation